The Effect of Numeration Literacy-Based Learning on Creative Thinking and Mathematical Communication Ability - Nurliah Nurliah; Agustan Syamsuddin; Idawati Idawati (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine the effect of numeracy literacy-based learning on students' creative thinking abilities and mathematical communication. This research is a quasi-experimental study with a nonequivalent control group design. The research population consisted of all fourth grade students in the cluster I area of ​​Somba Opu District, Gowa Regency with a total of 340 students. Through cluster random sampling, 46 students from SD Negeri Sungguminasa IV were selected as research samples. Data collection was carried out through questionnaires and tests. Data were analyzed through descriptive statistical analysis techniques and inferential statistics consisting of independent sample t tests and multivariate tests. The results showed that numeracy literacy-based learning had an effect on the ability to think creatively and mathematically communicate in class IV students at SD Negeri Sungguminasa IV, Gowa Regency.